LEGAL CERTAINTY FOR TWO-WHEELED VEHICLES WITH ENGINE CAPACITY ABOVE 500CC - Utomo Baruno, Wira Prio Utomo Baruno; Yumarni, Ani; Mulyadi (Fakultas Hukum Universitas Djuanda, 2024)
The need for legal certainty for two-wheeled vehicles, especially those with high cubic capacity or commonly called large motorbikes, especially in Indonesia. This study aims to determine the legal certainty for two-wheeled vehicles with engine capacity above 500cc. This research is classified as empirical legal research, namely research that examines community behavior as a legal issue. In this study, the object studied is deviant behavior in the form of disturbances to security and order. The results of the study show that vehicles with a cubic capacity above 500cc certainly have a very high thrust that can travel 100 kilometers per hour or even faster than four-wheeled vehicles. This has the potential to cause danger to users and of course has an impact on others if it causes an accident. Legal certainty is the existence of clear provisions of laws and regulations that regulate a legal issue that can be implemented so that it can provide rights to every citizen. Legal certainty certainly requires law enforcement from law enforcers to prevent, prosecute, and rehabilitate traffic violators so that they do not repeat their actions